Bi(OTf)3-catalyzed C–H bond functionalization of azaarenes for the facile access to oxindoles featuring quaternary carbon centers1. Issue 11 (7th February 2015) - Lu, Beili; Lu, Qilin; Zhuang, Senyang; Cheng, Jiajia; Huang, Biao
<x xml:space="preserve">Abstract</x> Bi(OTf)3-catalyzed sp3 C–H functionalization of 2-alkyl azaarenes to isatylidene malononitriles has been achieved to give oxindoles containing an all-carbon quaternary center.